ANALISIS DAN PENILAIAN TEKNOLOGI INFORMASI PADA PROSES TATA KELOLA DENGAN COBIT 5 PADA DOMAIN EDM STUDI KASUS UNIVERSITAS PERADABAN - Rito Cipta Sagitta Haryono (Indonesian Journal of Business Intelligence (IJUBI), 2019)
Information technology governance (IT Governance) in companies has an important role in maximizing information technology that has been implemented at the University. However, IT governance can have several problems due to IT being only a concern of the technical team because it does not get the attention of top management. Without good IT governance various problems will arise. The EDM domain (Evaluate, Direct, Monitor) is one of the COBIT 5 tools, which is to measure the level of capability of the governance process. This study aims to analyze and assess the IT governance process using COBIT 5 tools on the EDM domain (evaluate, direct, monitor) with the Self Assessment method with a case study of the Peradaban University. The results of the assessment using the capability level COBIT 5 approach indicate that PUKSI of Peradaban University has a capability level at Level 1 for the EDM01 process because process performance is not planned and not monitored, nor are the resources and information needed to carry out processes not identified, provided, allocated, and used. So that IT governance is not maximally used.